How the electrochemical impedance spectroscopy can deepen the understanding of supercapacitor performance - S. O. Zelinskyi; N. G. Stryzhakova; O. V. Gozhenko; Y. A. Maletin (Хімія, фізика та технологія поверхні, 2022)
Electrochemical impedance spectroscopy has been used for the characterization of electric double layer capacitors also known as supercapacitors. Specific surface area and pore size distribution for supercapacitor electrode materials and the results of impedance spectroscopy measurements for two types of commercially available nanoporous activated carbons and two graphene-type materials have been studied and compared with the results obtained from cyclic voltammetry and galvanostatic charge-discharge cycling the supercapacitor prototypes in different voltage ranges and at different current densities. It has been found that the results for the characteristics of studied supercapacitor prototypes differ insignificantly if they were obtained by different methods, while all three research methods have shown the advantage of materials with nanoporous activated carbon over materials of the graphene type. Besides, according to the data obtained by measuring impedance at low frequencies the deviations from ideal capacitive behaviour are more significant in case of graphene-type materials. Comparison of the three research methods used in this work shows that the method of impedance spectroscopy makes it possible to obtain the most complete and reliable information on the performance characteristics of the supercapacitor system, since not only the capacitance and resistance values, but their frequency dependence, as well as deviations (in degrees) from the purely capacitive vertical line at Nyquist plots and capacitance dissipation can be determined and taken into consideration.